Sequential Solvent Extraction of Caesalpinia pulcherrima Yellow Flowers Reveals Potent Antioxidant, Antimicrobial, and Anticancer Activities Against Various Human Cancer Cell Lines - Sirisarn, Wanchat; Mordmuang, Auemphon; Sukpondma, Yaowapa; Obchoei , Sumalee; Saeheng, Sompop (Trends in Sciences, 2025)
While the pursuit and development of novel drugs to combat emerging diseases is ongoing, many newly characterized compounds have been discovered in different parts of traditional medicinal plants. Numerous investigations have scrutinized the phytochemical properties of the leaf, flower, seed, and bark of Caesalpinia pulcherrima, revealing its noteworthy attributes as an herbal remedy employed in the treatment of diverse ailments. Our research aims to re-evaluate this medicinal plant, with a focus on the yellow flower, employing a sequential solvent extraction technique. Our findings revealed that a methanolic extract exhibited the highest antioxidant capacity in 3 colorimetric antioxidant assays: DPPH, ABTS, and FRAP. Extracts from the yellow flower of C. pulcherrima exhibited antimicrobial resistance against a wide range of both pathogenic Gram-positive and Acinetobacter baumannii isolates. Additionally, these extracts manifested anticancer properties against various cancer cell lines. Our investigation marks the first inhibition of cell proliferation of the bile duct cancer cell line (KKU-213A) by this crude extract. This study contributes valuable insights to the ongoing research of potential phytochemical properties from the yellow flower of C. pulcherrima, providing additional information for further research on the separation and purification of crude extracts from the yellow flower of C. pulcherrima. Ultimately, our study presents a promising approach to specifically screening phytochemicals from C. pulcherrima flowers that could be developed into new antibiotic drugs or anticancer agents. HIGHLIGHTS Methanol was identified as the most effective solvent for extracting antioxidant compounds from Caesalpinia pulcherrima yellow flowers. Extracts obtained using hexane, ethyl acetate, and aqueous solutions exhibited antimicrobial activity against all tested gram-positive bacteria and some gram-negative strains. For the 1st time, this study demonstrated that ethyl acetate and methanol extracts showed significant cytotoxicity against the bile duct cancer cell line KKU-213A, indicating their potential for anticancer drug development. GRAPHICAL ABSTRACT